Partially delocalized charge in Fe-doped NiCo2S4 nanosheet–mesoporous carbon-composites for high-voltage supercapacitors. Issue 33 (6th August 2019) - Lai, Feili; Feng, Jianrui; Heil, Tobias; Tian, Zhihong; Schmidt, Johannes; Wang, Gui-Chang; Oschatz, Martin
Abstract : Partially delocalized charge is generated in Fe-doped NiCo2 S4 nanosheets, which show significantly enhanced adsorption ability towards ionic liquid ions. Abstract : Unraveling the effect of transition-metal doping on the energy storage properties of bimetallic sulfides remains a grand challenge. Herein, we construct bimetallic sulfide nanosheets and hence deliberately introduce transition-metal doping domains on their surface. The resulting materials show not only an enhanced density of states near the Fermi level but also partially delocalized charge as shown by density functional theory (DFT) calculations. Fe-doped NiCo2 S4 nanosheets wrapped on N, S-doped ordered mesoporous carbon (Fe-NiCo2 S4 @N, S-CMK-3) are prepared, which show an enhanced specific capacitance of 197.8 F g −1 in ionic liquid-based supercapacitors at a scan rate of 2 mV s −1 . This is significantly higher as compared to the capacitance of 155.2 and 135.9 F g −1 of non-iron-doped NiCo2 S4 @N, S-CMK and Fe-NiCo2 S4 @CMK-3 electrodes, respectively. This result arises from the enhanced ionic liquid polarization effect and transportation ability from the Fe-NiCo2 S4 surface and N, S-CMK-3 structure. Furthermore, the importance of matching multi-dimensional structures and ionic liquid ion sizes in the fabrication of asymmetric supercapacitors (ASCs) is demonstrated. As a result, the ASC device exhibits a high energy density of 107.5 W h kg −1 at a power density of 100 W kg −1 in a working-voltage window of 4 V when using Fe-NiCo2 S4 @N, S-CMK-3 and N, S-CMK-3 as positive and negative electrodes, respectively. This work puts forward a new direction to design supercapacitor composite electrodes for efficient ionic liquid coupling.